Association between infant Feeding Practices and Insulin – Dependent Diabetes Mellitus (IDDM) - Hussein, Kahtan (Iraqi National Journal of Nursing Specialties, 2005)
Abstract The percent study aimed to determination the association between infant feeding practices and Insulin-Dependent Diabetes Mellitus (IDDM). The study was conducted at (he National Center of Diabetes in Baghdad City the Capital of Iraq throughout the period of January 2001 to January 2002. The sample was comprised of (200) mother of Insulin-Dependent Diabetes Mellitus (IDDM) of children under age of 12 years old. Data was collected through the use of a questionnaire that constructed by researcher and which were developed for the purpose of the present study. Reliability of the instruments was determination through use of person correlation coefficient for the test- retest approach was (0.87) and the instruments validity was determined through content validity which was determined by a panel of expert. Analysis of data was performed through the application of descriptive statistics. The study result had revealed that the majority of diabetic children are bottle-feeding and the lowest are breast feeding, these findings mean that is association between infant feeding practices and the incidence of Insulin - Dependent Diabetes Mellitus (IDDM). The study concluded that the diabetes mellitus was highly incidence among children of artificial feeding and low incidence among children of breast-feeding. It was also recommended that the duration of breast-feeding should be continuous at least until the first six mouths of the child age especially those of families at risk of Diabetes.